Meningkatkan Kedisiplinan Mahasiswa Manggarai dengan Self Management - Eleonora Sunarti Dahul; Romia Hari Susanti; Laily Tiarani Soejanto (JKI (Jurnal Konseling Indonesia), 2022)
Discipline is visible student behavior. Discipline is formed through values, customs, rules and norms that apply in society. Therefore, as a student, wherever he is from, he is obliged to apply discipline wherever he is studying. This study aims to improve the discipline of Manggarai students who are currently studying at Universitas PGRI Kanjuruhan Malang, because these students in the initial study of the research showed a low level of discipline. This study applied a pre-experimental design with one group pre-test and post-test design. The sampling technique used is purposive sampling. The researcher determined five students as research subjects who had fulfilled the purposive sampling requirements from the pretest results. This research instrument applies a disciplinary scale and group counseling guidelines so that the research process and results can be obtained optimally according to the researchers' expectations. The results of the study showed differences in the average scores of students' discipline pretest and posttest, where students received a low pretest and a high posttest. Furthermore, the results of the Wilcoxon test analysis show a probability score that is smaller than 0.05, meaning that self-management techniques can improve student discipline.